An empirical study on users' adoption of MOOCs from the perspective of the institutional theory. (2016) - Gao, Shang; Yang, Yuhao
MOOC, which stands for massive open online course, has attracted millions of users around the world and it has a promise to be a very important element of future education. However, there is a little research on users' adoption of MOOCs. This paper aims to improve the understanding of users' behaviour intention to use MOOCs. The proposed research model is an extension of technology acceptance model with three factors from the institutional theory. And an empirical study with 279 subjects was conducted to test this model in China. The results indicate that both perceived usefulness and perceived ease of use directly affect users' behaviour intention to use MOOCs significantly. Another interesting finding is that mimetic pressures also have a significant positive influence on users' behaviour intention to use MOOCs.